(3ahGJ GdhajGJs - (3eMeO Hf TGcQ Hf CMeO Hf YHO GdQMef GdcJHj GdOGQGfqj GdOeTbqj, UdGM GdOjf , GHf TGcQ J (B764 (3g` s
(3ChdgG (B:s
(3jHOC HJQLeI QGTO Hf ESMGb Hf QGTO CHj eMeO GdcGJH GdCfHGQi GdedbH HCHi McjeI s
(3BNQgG (B:s
(3jfJgi HJQLeI TjN GdTjhN HMeGI YHO GdYRjR Hf eMeO Hf YHO GdeMSf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B1185s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1292s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ , HgG NQe s
Keywords: (3GdJGQjNs